Candida krusei Empyema Thoracis: A Community-Acquired Infection Requiring a High Index of Suspicion - Hazim Bukamur; Waseem Ahmed; Yazan Numan; Ibrahim Shahoub; Fuad Zeid (Case Reports in Infectious Diseases)
Empyema thoracis is a serious condition characterized by the accumulation of purulent fluid in the pleural cavity, typically following a pneumonia, subdiaphragmatic abscess, or esophageal rupture. Fungal empyema thoracis is a rare form of this condition with especially high mortality, in which the most frequently isolated fungus is Candida spp. This article presents a 74-year-old female with Candida krusei pneumonia and a complicated hospital course, initially presenting with nausea, vomiting, and dysphagia. She was initially suspected to have community-acquired pneumonia and was started on azithromycin and ceftriaxone. Worsening respiratory function led to the diagnosis of hydropneumothorax. Pleural fluid and an independent sample of pus and pleural tissue grew Candida krusei, giving the diagnosis of fungal empyema. With further respiratory deterioration, the patient was intubated and switched to piperacillin/tazobactam and micafungin. Decortication with extensive pleural peel and removal of foul-smelling pus and food particles within the chest was performed. This further lead to confirmation of esophageal perforation, and she was started on voriconazole and meropenem. After developing septic shock, the patient was managed with phenylephrine and vasopressin. Finally, after improving she was weaned off pressors and extubated, followed by an esophagogastroduodenoscopy (EDG) with pneumatic balloon dilation and WallFlex stent placement. This patient’s case demonstrated an example of empyema thoracis, which required a high index of suspicion since the presentation was with a community-acquired infection. Candida empyema thoracis may be a complication of operation, gastroesophageal fistula, and spontaneous esophageal rupture. On the other hand, the course of this patient’s hospital stay progressed from esophageal perforation to Candida krusei pneumonia, empyema, and pneumothorax. Thus, community-acquired fungal empyema should be considered in patients with respiratory symptoms and suspected esophageal perforation; nevertheless, after a diagnosis of fungal empyema, esophageal perforation should also be ruled out in addition to other causes like pneumonia, subphrenic abscess, and hematogenous spread. Improved communication between clinicians and microbiologists can lead to early diagnosis and a reduction in the morbidity and mortality of this condition.